CHARACTERISTICS OF THE FAR EASTERN POPULATION OF TICK-BORNE ENCEPHALITIS VIRUS AND SOLVING ISSUES OF SPECIFIC PREVENTION - G. N. Leonova (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
The subdivision of the viral population into subtypes and clusters based on the molecular genetic characteristics of the tick-borne  encephalitis virus (TBEV) strains predetermines not only the  differences in the biological properties of these strains, but also their different responses to specific antibodies in persons vaccinated against TBE.The aim of the present study is to show the differences in biological properties on the model of two strains of Far Eastern TBEV subtype  belonging to different clusters and to substantiate the need for a  personalized approach to the vaccine prophylaxis of tick-borne encephalitis.Results. Two strains of TBEV were used in the studies. On the basis of full genome sequencing the Dal’negorsk strain (FJ402886,  GenBank) is referred to the typical representative of Sofjin-like, and  Primorye-437 (JQ825162, GenBank) – to Oshima-like TBEV strains  of the Far Eastern subtype.The experiment shows the levels of  specific antibodies capable of neutralizing virulence strains of tick- borne encephalitis virus. Low antibody titers (1:100 and 1:400) can  neutralize only a low dose of a non-virulent strain of tick-borne  encephalitis virus. Reliable protection against the disease of people infected with virulent strains of the TBEV can provide only a  high level of specific antibodies.Conclusion. If the level of specific antibodies of IgG is 1:400 or lower, the vaccination course should be continued, at a titer of  antibodies above 1:400, revaccination can be postponed subject to  annual monitoring of specific immunity parameters in the pre-epidemic TBE season.